A STUDY OF MORTALITY AND COMPLICATION RATE OF DIABETICS WITH MYOCARDIAL INFARCTION - Khattak, Mohammad Tahir; Javed, Mohammad (Journal of Ayub Medical College Abbottabad, 1993)
ABSTRACT: Diabetes Mellitus is a common endocrine disorder. Ii increases and accelerates atherogenesis. Cardiovascular complications dominate the lives of diabetic patients, with most succumbing to coronary artery disease. We studied the mortality and major complication rate of diabetics who developed an acute myocardial infarction. 26.4% of patients died during the index infarction and overall about 79% had at least one significant myocardial infarction related complication. Diabetic patients with a myocardial infarction need to be treated as a special group with close monitoring of their blood sugar levels to reduce the incidence of mortality and complications. Efforts should be made to prevent diabetes mellitus by the avoidance or treatment of obesity and by encouraging physical activity.